Diameter-Axial-Polar Nephrometry is Predictive of Surgical Outcomes Following Partial Nephrectomy. Issue 30 (July 2015) - Li, Mingmin; Gao, Yi; Cheng, Jiwen; Qu, Le; Chen, Junming; Cai, Chen; Xu, Bing; Li, Peng; Bao, Yi; Xu, Zhipeng; Xu, Yifan; Wu, Dengshuang; et al.
<x xml:space="preserve">Abstract</x> Abstract This study sought to evaluate the predictive value of the DAP (diameter-axial-polar) nephrometry system on surgical outcomes following partial nephrectomy (PN). This was a retrospective study of 237 patients who underwent open or minimally invasive PN for renal tumors at a single tertiary care center between 2009 and 2013. The primary outcomes included ischemia time >20 minutes and percentage of estimated glomerular filtration rate (eGFR) decline >10%. Statistical analysis was performed to study associations and predictions. The DAP sum score exhibited a statistically significant correlation with ischemia time, operative time (OT), estimated blood loss (EBL), length of hospital stay (LOS), and percent change in eGFR. The DAP sum score (odds ratio [OR]: 1.749; 95% confidence interval [CI] 1.379–2.220; P < 0.001) and conventional laparoscopy and laparo-endoscopic single-site (CL&LESS) surgery versus the open surgical approach (OR: 5.736; 95% CI: 2.529–13.011; P < 0.001) independently predicted an ischemia time >20 minutes. Similarly, the DAP sum score (OR: 1.297; 95% CI 1.051–1.602; P = 0.016), age-weighted Charlson comorbidity index (CCI) (OR: 4.730; 95% CI 1.463–15.291; P = 0.009), EBL (OR 2.433; 95% CI 1.095–5.407; P = 0.029), and ischemia time (OR 3.332; 95% CI 1.777–6.249; P < 0.001) were identified as independent predictors of eGFR decline >10%. Furthermore, the DAP score × ischemia time interactions were statistically significant (P < 0.001). We confirmed the predictive value of the DAP nephrometry score with respect to ischemia time and renal functional decline in an independent external cohort of patients undergoing PN. The effect of the DAP score on renal functional decline partially depends on that of ischemia time, and the individual component DAP scores may have different effects on clinical outcomes.